Zenker’s diverticulum — a case report - Bist, S. S. (Springer-Verlag, 2009)
A Zenker’s diverticulum is a blind pouch that branches off the cervical esophagus. Affected individuals may suffer from long-standing swallowing difficulties, regurgitation, bad breath, weight loss, and even aspiration.. Here we report a 80-years-old male presenting with dysphagia and regurgitation. Barium swallow reported the presence of a Zenker’s diveticulum. In view of the patient’s age, endoscopic diathermy was considered as a therapeutic option for the management.